Dust of the Land - Fletcher, J.H. (Australia Harlequin Mira, 2014)
There was only one way she could guarantee her future ... and she knew that she would take it. Bella Tucker has come a long way. Born illegitimate and banished to the London slums by her vindictive stepmother, at six Bella is rescued by her grandfather and brought up as a member of the aristocratic Richmond family. Her future seems assured when she falls passionately in love with Charles Hardy, heir to the wealthy Hardy estate - until her grandfather's death changes everything ... Heartbroken and headstrong, Bella flees to Australia, where she is offered a job by the charismatic Garth Tucker, owner --of Miranda Downs, a vast cattle station in the stunning and remote Pilbara region. After several near disasters, she finds herself falling in love with Garth amidst the dust, heat and the endless expanse of bush. Together, Bella and Garth become major players in the new mining industry, allowing Bella to build her dream home, the sprawling homestead, 'Desire'. But after Garth's unfortunate death, Bella is forced to deal with circumstances that bring the family close to ruin ... and the business Bella and Garth have built to the brink of collapse. Can Bella untangle the lies and save the business and her family home? And will she ever lay eyes again on the man she never ceased to love, Charles Hardy? Dust of the Land is an epic saga of one woman's strength through her trials in love and betrayal on Australia's red frontier.
Keywords: Australia -- Country life -- Ranches